2021
DOI: 10.1186/s12905-021-01187-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum antioxidant vitamin concentrations and oxidative stress markers associated with symptoms and severity of premenstrual syndrome: a prospective cohort study

Abstract: Background It has been suggested that premenstrual syndrome (PMS) may derive from either elevated oxidative stress or reduced antioxidant vitamin levels in the body; however, these relationships have been minimally studied in a large cohort of healthy women. Our objective was to estimate the association between serum concentrations of antioxidant vitamins (A, C, and E) and markers of oxidative stress (F2-isoprostane) with symptoms and severity of PMS. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
1
13
0
3
Order By: Relevance
“…Results from previous studies on vitamin A and premenstrual symptoms have been inconsistent. Frankel and colleagues recently evaluated the relationship between serum antioxidant vitamins, such as vitamins A, C and E, and PMS in 259 healthy women aged 18-49 in western New York, U.S.A [21]. There were no associations between serum vitamin A, measured using retinol as a biomarker, and the prevalence or the severity of PMS, a result that is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Results from previous studies on vitamin A and premenstrual symptoms have been inconsistent. Frankel and colleagues recently evaluated the relationship between serum antioxidant vitamins, such as vitamins A, C and E, and PMS in 259 healthy women aged 18-49 in western New York, U.S.A [21]. There were no associations between serum vitamin A, measured using retinol as a biomarker, and the prevalence or the severity of PMS, a result that is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…The present cross-sectional study of 553 young women living in Canada examined the association between plasma carotenoids and retinol on the severity of 15 common premenstrual symptoms. While previous research on this topic assessed retinol alone [19][20][21][22], the current study included six different plasma carotenoids along with retinol to provide a more comprehensive understanding of the role of vitamin A and provitamin A carotenoids, which may have unique biological effects. Further, using serum concentrations as opposed to dietary intake allowed a more direct measure of exposure as serum values take into account the variability of an individual's metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These new findings were confirmed in an up-to-date systematic review 102 . Moreover, a recent prospective study showed that serum concentrations of antioxidant vitamins A, C, and E were generally not associated with PMS symptoms or severity, supporting the evidence that the use of antioxidant vitamins as a remedy for PMS may be inconclusive 103 . On the other hand, zinc supplementation manifested different properties on inflammation and premenstrual symptoms.…”
Section: Inflammationmentioning
confidence: 90%